The 10th international conference on "Photosynthesis and Hydrogen Energy Research for sustainability": A pictorial report in honor of Tingyun Kuang, Anthony Larkum, Cesare Marchetti and Kimiyuki Satoh. (29th November 2019) - Borisova-Mubarakshina, Maria M.; Tsygankov, Anatoly A.; Tomo, Tatsuya; Allakhverdiev, Suleyman I.; Eaton-Rye, Julian J.; Govindjee, Govindjee
Abstract: An international Conference « Photosynthesis and Hydrogen Energy Research for Sustainability » is a traditional event held in various countries of the world. We present here a pictorial report of the 10th Conference, held in St. Petersburg (Russia), during June 23–28, 2019, in honor of four distinguished international scientists: Tingyun Kuang (China), Anthony Larkum (Australia), Cesare Marchetti (Italy), and Kimiyuki Satoh (Japan). In the present news report, we provide a description of the conference, scientific program and special events, as well as a brief introduction and contributions of those honored. Special attention is given to the event that was organized for young researchers who were chosen for their outstanding research in the field of photosynthesis and hydrogen energy. Several photographs are included to show the excellent atmosphere of the 10th Conference.